Evidence for broad cross-reactivity of the SARS-CoV-2 NSP12-directed CD4+ T-cell response with pre-primed responses directed against common cold coronaviruses - Westphal, Tim; Mader, Maria; Karsten, Hendrik; Cords, Leon; Knapp, Maximilian; Schulte, Sophia; Hermanussen, Lennart; Peine, Sven; Ditt, Vanessa; Grifoni, Alba; Addo, Marylyn Martina; Huber, Samuel; et al. (Frontiers in Immunology, 2023)
The Non-Structural Protein 12 (NSP12) of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has a high sequence identity with common cold coronaviruses (CCC). Here, we com-prehensively assessed the breadth and specificity of the NSP12-specific T-cell response after in vitro T-cell expansion with 185 overlapping 15-mer peptides covering the entire SARS-CoV-2 NSP12 at sin-gle peptide resolution in a cohort of 27 COVID-19 patients. Samples of nine uninfected seronegative individuals, as well as five pre-pandemic controls were also examined to assess potential cross-reactivity with CCC. Surprisingly, there was a comparable breadth of individual NSP12 peptide-specific CD4+ T-cell re-sponses between COVID-19 patients (mean: 12.82 responses, range 0-25) and seronegative controls including pre-pandemic samples (mean: 12.71 responses, range 0-21). However, the NSP12-specific T-cell responses detected in acute COVID-19 patients were on average of a higher magnitude. The most frequently detected CD4+ T-cell peptide specificities in COVID-19 patients were aa236-250 (37%) and aa246-260 (44%), whereas the peptide specificities aa686-700 (50%) and aa741-755 (36%) were the most frequently detected in seronegative controls. In CCC-specific peptide-expanded T-cell cultures of seronegative individuals, the corresponding SARS-CoV-2 NSP12 peptide specificities also elicited responses in vitro. However, the NSP12 pep-tide-specific CD4+ T-cell response repertoire only partially overlapped in patients analyzed longitudinal-ly before and after a SARS-CoV-2 infection. The results of the current study indicate the presence of pre-primed, cross-reactive CCC-specific T-cell responses targeting conserved regions of SARS-CoV-2, but also underline the complexity of the analy-sis and the limited understanding of the role of the SARS-CoV-2 specific T-cell response and cross-reactivity with the CCCs.